Solubility enhancement of indigo dye through biochemical reduction and structural modification - Park, Hyun A.; Kim, Ha Yan; Chauhan, Sushma; Sudheer, Pamidimarri D.V.N.; Choi, Kwon Young (Korean Journal of Chemical Engineering, 2022)
Indigo is one of the most widely used dyes for textiles and is thus produced in large quantities. Owing to its low solubility, a chemical-dependent continuous reduction-oxidation process is often used for indigo dyeing. Unfortunately, the indigo dyeing process has adopted a hazardous reducing agent such as Na2S2O4, to reduce indigo into leucoindigo, thus causing serious water pollution in the process. To avoid this, the use of chemical reducing reagents was banned, creating a need to identify alternative reducing agents or to develop more eco-friendly dyeing processes. In this review, alternative reducing reagents such as biochemicals, plant fruits, biocatalysts, and microbes, which are less harmful to the environment than chemical reducing reagents, are summarized with their reducing reactions and performance. In addition, alternative modifications of indigo that bypass the use of reducing reagents have also been briefly introduced. The reducing chemicals and processes summarized have their respective merits and drawbacks; however, further research is required to obtain profitable dyeing performance that meets economic goals.
Keywords: Eco-friendly; Indigo; Indigo Dyeing; Indigo Reduction; Reductase